The impacts of digital payment capability on food consumption upgrading in rural households: evidence from China - Zhou, Chao; Wang, Shiyuan; Zhou, Lei; Wan, Shenwei (Frontiers in Nutrition, 2025)
Globally, rural areas in developing countries face food insecurity and malnutrition, threatening both public health and sustainable development. This study examines the impact of digital payment capability (DPC) on the upgrading of food consumption pattern (UFCP) among rural Chinese households. Guided by Sen’s Feasible Capability framework, we construct a multidimensional DPC index comprising information access, liquidity access, digital engagement and external training. We apply this index to 2,078 households from the China Rural Revitalization Survey (CRRS) and adopt the Ford Behavioral Model to analyze both direct effects and mediating pathways. Our main findings are as follows. First, DPC significantly enhances UFCP, with the effect largely mediated by increases in household income and improvements in the health awareness of household heads. Second, the positive association between DPC and UFCP is strongest in eastern and western provinces, in peri-urban areas and in regions with more advanced digital economies. Third, dietary gains from higher DPC are most pronounced in households led by middle-aged, less-educated or less-healthy individuals, and in families with middle to high incomes. These results underscore the potential of digital payment services to drive dietary transformation in rural China. To maximize impact, policymakers should expand digital-payment infrastructure and pair it with targeted income-support and health-literacy programs, thereby fostering more diverse diets and greater well-being in rural populations.